The influence of brand image, halal label, and religiosity on the purchasing attitude of local halal cosmetics in Bogor - Aliza, Putri; Akbar , Nashr (Universitas Islam Indonesia, 2024)
IntroductionIn the rapidly growing cosmetics industry, consumers are becoming increasingly conscious of the quality and halal certification of the products they use. People living in Bogor, especially those with strong religious orientations, tend to seek cosmetics that meet quality standards and align with their religious values.ObjectivesThis study examines the influence of brand image, halal label, and religiosity on the purchasing attitude of local halal cosmetics in Bogor.MethodThis quantitative descriptive research employs the SEM-PLS approach, utilizing Smart PLS version 3.0 software. The sample data comprises 105 respondents.ResultsThe results of the F-test showed that the significance value (sig) is 0.000 < 0.05, indicating that brand image (P-value = 0.048), halal label (0.000), and religiosity (0.000) significantly and positively influence the purchasing attitude of local halal cosmetics.ImplicationsThis research provided insights for local halal cosmetics companies on the importance of brand image and the halal label of their products for customers. For policymakers, it highlights the importance of halal regulation to protect customers from using non-halal cosmetics products.Originality/NoveltyThis study provides insights into the purchasing attitude of Muslims regarding cosmetics products in Indonesia.